1976
DOI: 10.1161/01.cir.53.3.400
|View full text |Cite
|
Sign up to set email alerts
|

The role of the renin-angiotensin-aldosterone system in cardiovascular homeostasis in normal human subjects.

Abstract: SUMMARY To examine the role of angiotensin II in the maintenance of blood pressure and the control of aldosterone secretion in man, eight normal subjects were studied on a tilt table in sodium replete and sodium depleted states prior to and subsequent to the intravenous infusion of an angiotensin converting enzyme inhibitor (CEI). In both the sodium replete or sodium depleted state, upright tilting resulted in an increase in heart rate and a narrowing of pulse pressure. None of the sodium replete or depleted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(57 citation statements)
references
References 30 publications
5
52
0
Order By: Relevance
“…However, in the experiments of Aiken and Vane, All and norepinephrinie were infused into the renal artery for 5-6 min, a duration of time adequate to induce prostaglandin synthesis in response to the vasoconstrictor actioni of the two hormones (21). On the other hand, in the present experiimient, All and( inorepinephriine were injected as bolus injectionis and the maximal reduction of renial blood flow (which almost always occurred withiin [5][6][7][8][9][10] In summary, the present studies demonstrate that the renal vascular reactivity to Al, was blunted by acute or chronic sodium depletion (which stimulates renin secretion) and was enhanced by acute sodium repletion or chronic administration of a high salt diet and DOCA (which suppress renin secretion) or by CEI (which presumably reduced the concentration of circulating All). The renal vascular reactivity to norepinephrine was not significantly influenced by alteration of sodium balance or by administration of converting enzyme (except for an enhancement of norepinephrine sensitivity which occurred after CEI in dogs pretreated with DOCA and salt).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…However, in the experiments of Aiken and Vane, All and norepinephrinie were infused into the renal artery for 5-6 min, a duration of time adequate to induce prostaglandin synthesis in response to the vasoconstrictor actioni of the two hormones (21). On the other hand, in the present experiimient, All and( inorepinephriine were injected as bolus injectionis and the maximal reduction of renial blood flow (which almost always occurred withiin [5][6][7][8][9][10] In summary, the present studies demonstrate that the renal vascular reactivity to Al, was blunted by acute or chronic sodium depletion (which stimulates renin secretion) and was enhanced by acute sodium repletion or chronic administration of a high salt diet and DOCA (which suppress renin secretion) or by CEI (which presumably reduced the concentration of circulating All). The renal vascular reactivity to norepinephrine was not significantly influenced by alteration of sodium balance or by administration of converting enzyme (except for an enhancement of norepinephrine sensitivity which occurred after CEI in dogs pretreated with DOCA and salt).…”
Section: Resultsmentioning
confidence: 67%
“…During sodium depletion, there is an increase in the concentration of circulating angiotensin II (1). The administration to sodium-depleted animals or to huimans of pharmacological agents that prevent the formation of angiotensin 11 (All)' or that compete with this polypeptide for its vascular receptors, induces a drop in arterial blood pressure with little or no change in cardiac output (2)(3)(4)(5). Despite the fact that the vasoconstrictor action of Al appears to be essential for the maintenance of normal blood pressure during sodium depletion, the pressor and vascular responses to exogenously administered octapeptide are greatly reduced in this condition (6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…These peptides have been assigned important roles in the regulation of blood pressure and transvascular fluid exchange by several investigators (4)(5)(6)(7)(8). Using a blood pressure response bioassay in intact, anesthetized dogs, we demonstrated that acute alveolar hypoxia impaired AI conversion (9).…”
Section: Abstract Endothelial Cells In Tissue Culturementioning
confidence: 83%
“…The majority (~90%) of them lived most of their lives and were born in the same area of Spain (Meseta Castellana,~600 m altitude). (Zintzaras et al 2008;Sancho et al 1976), ischemic stroke (Slowik et al 2007) type II diabetes (Zhou et al 2009 Cardiorespiratory fitness in CAD (Defoor et al 2006;Wagoner et al 2002) 0 = GG, 1 = CG, 2 = CC ADRB2 Adrenergic, beta-2-, receptor…”
Section: Methodsmentioning
confidence: 99%